Analisis Kemampuan Berpikir Kritis Mahasiswa Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Nias dalam Menyelesaikan Soal Higher Order Thinking Skills (HOTS) - Sadiana Lase (Medan Resource Center, 2026)
Critical thinking is an essential competency for prospective mathematics teachers, yet many students continue to experience difficulties in solving Higher Order Thinking Skills (HOTS) problems. This study aimed to analyze the critical thinking skills of Mathematics Education students at the Faculty of Teacher Training and Education, Universitas Nias, in solving HOTS problems. A descriptive qualitative approach was employed involving 40 fourth-semester students selected through purposive sampling. Data were collected using HOTS tests, semi-structured interviews, and observations, and analyzed using the Miles and Huberman interactive model. The findings revealed that students' critical thinking skills remained low, with an average achievement of 46.7% based on Facione's indicators. The weakest dimensions were evaluation (35.8%) and self-regulation (38.9%), while the greatest difficulty in Bloom's revised taxonomy occurred at the creating level (70.3%). Metacognitive errors (86.7%) and transformation errors (80.0%) dominated students' responses, indicating limitations in reflective thinking and mathematical modeling. The study concludes that Mathematics Education students require pedagogical interventions emphasizing metacognitive scaffolding and open-ended problem-solving to strengthen critical thinking and Higher Order Thinking Skills competencies.